The motivation of physical education college students to become teachers after graduation - Sindiani, Mahmood; Tsuk, Sharon (Frontiers in Education, 2025)
PurposeThis study examines the motivations and reservations of undergraduate Physical Education Teacher Education (PETE) students regarding their future careers as schoolteachers and identify key factors influencing their career intentions.MethodA repeated cross-sectional survey utilized data from 443 PETE students across four academic years. Surveys included both quantitative and qualitative questions, administered at two time points within an academic year.ResultsFindings revealed that 69% of participants expressed interest in teaching; however, this declined significantly among upper-year students. No differences emerged between the two data collection points. Factors such as personal satisfaction, economic concerns, and perceived support systems influenced the motivation to become schoolteachers.Discussion/conclusionThe integration of findings highlights the need for enhanced teacher education programs, focusing on professional development and realistic career previews. These findings aim to refine curricula and support the preparation of dedicated PE teachers.